Amyloidosis: a unifying diagnosis for nephrotic syndrome and congestive cardiac failure. (27th August 2018) - Sara, Jaskanwal Deep Singh; Khodadadi, Ryan; Barth, Dylan; Burton, Mary Caroline
Abstract : Diagnosing patients simply with heart failure or nephrotic syndrome is insufficient, and clinicians should always search for the underlying causes of these syndromes. Amyloidosis represents a rare group of diseases in which abnormal protein, namely amyloid fibrils, build up in various organs. Presentation depends on which organ systems are involved, and symptoms could include breathlessness associated with fluid overload suggestive of cardiac and/or renal involvement and diarrhoea and weight loss, suggestive of gastrointestinal involvement. The authors present a case of congestive cardiac failure and nephrotic range proteinuria in a patient with persistent fluid overload secondary toamyloid light-chain (AL) amyloidosis.